Implementasi Metode Manhaji dalam Pembelajaran Nahwu Shorof di Manhaji Course - Sholikha, Mahma Amila (Academica : Journal of Multidisciplinary Studies, 2018)
AbstractThrough a good understanding of the Arabic language, it will be able to be equipped in understanding the Qur'an and Hadith. Understanding Arabic cannot be separated from studying nahwu shorof. But in learning it, of course there are certain methods that can help to make it easier to understand. Therefore, in this study the author will examine the implementation of the Manhaji method in learning nahwu shorof on the manhaji course. The research method used is a qualitative method that is descriptive analytical. The results of the study note that there is an implementation of learning nahwu shorof in Manhaji Course which is different from other methods. The most striking difference is that this method is more enjoyable in learning, overall, examples taken directly from the Qur'an, complete and general for all groups and various levels, focusing on tarjamah al-Qur'an, translating nahwiyah with the dhomir mentioned for the word berkhomir.Keywords: Arabic, Hajj method